Performa Anak Hasil Persilangan antara Induk Sapi PO dengan Bangsa Pejantan yang Berbeda di Wilayah Inseminasi Buatan (IB) di Kecamatan Terbanggi Besar Kabupaten Lampung Tengah - M. D. I. Hamdani; Sulastri Sulastri; T. Rumiyani (State Islamic University of Sultan Syarif Kasim Riau, 2020)
The research investigates to know performance of calf from Crossing between Peranakan Ongole (PO) dams with some of the bull at one years age. Located of research in Terbanggi Besar District, Central Lampung Regency. This research was doing in May until August 2018. Material of research are 30 head PO Cattle, 30 head Simmental><PO; 30 head Limousin><PO. Variable of research are body length, shoulder height, chest circumference and body weight. Qualitatif performance variables are colour of skin, type of head, type of face, hump, hides cattle, and horn type. Qualitative data analyzed by descriptive analysis, and quantitative data analyzed by t-test. The result of research showing calf qualitative performance has different in every bull. Body weight of cattle for each are PO cattle (248,36± 24,89kg); calf from Simmental><PO cattle (257,08± 27,88kg) and it’s showing significant different (P<0.05); calf from Limousin><PO cattle (252,25± 32,51kg). The body measurment for each cattle showing variation.